Agro-Chain Greenhouse Gas Emissions (ACE) calculator - Broeze, Jan (2019)
The Agro-Chain Greenhouse Gas Emissions (ACE) calculator is a tool for estimating total greenhouse gas emissions associated to a food product. It addresses the most common stages of ‘linear’ agro-food chains (chains for fresh and simple processed products: canned, frozen, packaged and other minimal processed forms). It combines a calculation framework with datasets containing crops greenhouse gas emission factors and food loss factors along the chain. Combined with user-definition parameters for the product-chain considered, it generates an estimate for greenhouse gas emissions associated to a product when bought by a consumer. The default data that the calculator derives from the dataset may be overruled by the user if more specific data are available; this would make the calculations more case-specific. The calculator works on a personal computer as well as a mobile phone (both in Microsoft Excel). Full instructions are provided on the first worksheet of the calculator.